2000
DOI: 10.2343/geochemj.34.383
|View full text |Cite
|
Sign up to set email alerts
|

Determination of lanthanoids and yttrium in JGb2 and JR3 by inductively coupled plasma-mass spectrometry after cation-exchange pretreatment.

Abstract: The lanthanoids (Ln) and yttrium (Y) in rock standard samples issued from the Geological Survey of Japan (GSJ) have been determined by inductively coupled plasma-mass spectrometry (ICP-MS). Sample solutions of two igneous rocks, JGb2 and JR3, with no certified values for Ln and Y were prepared using acid digestion technique, and the Ln and Y were separated from other constituents by a cation-exchange column pretreatment. Corrections for polyatomic interference ions were made for the precise and accurate determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Cation-exchange resin methods before REE + Y measurements using ICP-MS techniques are required in some specific cases to precisely and accurately determine REE + Y contents, such as accurate measurements of geological reference materials (JGb2 leucogabbro and JR3 peralkaline rhyolite from the Geological Survey of Japan) (Lee et al 2000). This also ensures a pre-concentration of REE in highly depleted lithologies, such as ultra-depleted REEs in peridotites (Ulrich et al 2012), or REE separation from highly charged matrix such as salts (Steinman et al 2001).…”
Section: Sample Preparation Of Rocks Minerals and Natural Fluids For Icp-ms Determination Of Reementioning
confidence: 99%
“…Cation-exchange resin methods before REE + Y measurements using ICP-MS techniques are required in some specific cases to precisely and accurately determine REE + Y contents, such as accurate measurements of geological reference materials (JGb2 leucogabbro and JR3 peralkaline rhyolite from the Geological Survey of Japan) (Lee et al 2000). This also ensures a pre-concentration of REE in highly depleted lithologies, such as ultra-depleted REEs in peridotites (Ulrich et al 2012), or REE separation from highly charged matrix such as salts (Steinman et al 2001).…”
Section: Sample Preparation Of Rocks Minerals and Natural Fluids For Icp-ms Determination Of Reementioning
confidence: 99%
“…[28] Pretreatment of samples, correction standards and other techniques such as Raman and X-ray fluorescence have also been used to measure REE in geological samples. [29][30][31][32][33] Although the measurement of REE by ICP-MS is demonstrated to be accurate and reproducible, the proper preparation of materials for ICP-MS is crucial for accurate results. A comparative study of REE in geological reference materials using INAA and ICP-MS showed that ICP-MS was more accurate for light REE (La-Gd) compared to heavy REE (Tb-Lu), but determined that INAA produced results closer to literature values and suggested that sample preparation for ICP-MS was the cause.…”
Section: Introductionmentioning
confidence: 99%
“…× 42 mm) was used for REE group separation. The volume of the ion-exchange resin used this study is 1/10 of that in Lee et al (2000), significantly reducing the volume of eluant and the experimental time needed for REE group separation, and minimizing the REE blank from reagents. The sample dissolved in the mixed acid was loaded onto the cation-exchange column that had been previously conditioned by 2 ml of 2M HNO 3 .…”
Section: Sample Dissolution and Matrix Removalmentioning
confidence: 99%
“…Therefore, the pretreatment of sample using an ion-exchange column is generally carried out in the HPIC/HPLC analysis (Cassidy, 1988;le Roex and Watkins, 1990;Watkins and le Roex, 1992;Asahara et al, 1995;Na et al, 1995). The procedure of matrix removal used in this study is the modified version of the method described in Lee et al (2000). 1 ml of cation exchange resin (BioRad AG 50W X12, 200-400 mesh) packed in Muromac polypropylene column (5.0-5.5 mm i.d.…”
Section: Sample Dissolution and Matrix Removalmentioning
confidence: 99%